ANALYSIS OF THE RESTRUCTURING OF THE MUSYARAKAH MUTANAQISAH CONTRACT IN THE DECISION OF THE RELIGIOUS COURT BASED ON THE FATWA DSN-MUI/89/XII/2013 - Diah Sisca Anggraini; Mustapa Khamal Rokan (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the financing restructuring regulations in the Musyarakah Mutanaqisah (MMQ) contract based on Financial Services Authority Regulation Number 2/POJK.03/2022, and examine the legal considerations of the panel of judges in the Medan Religious Court Decision Number 1224/Pdt.G/2024/PA.Mdn and the Demak Religious Court Decision Number 4/Pdt.G.S/2024/PA.Dmk reviewed from the perspective of the DSN-MUI Fatwa Number 89/XII/2013 concerning Sharia Financing Restructuring. This study uses a normative juridical method with a statutory approach, a case approach, and a conceptual approach. The results show that POJK Number 2/POJK.03/2022 provides a normative framework for Islamic banks to restructure problematic financing through rescheduling, reconditioning, and restructuring mechanisms while still observing the principles of prudence and sharia compliance. In the Demak Religious Court Decision, the panel of judges considered that the bank had attempted restructuring through an addendum to the agreement as a form of rescheduling, so that the legal considerations used were in line with the principles of the DSN-MUI Fatwa Number 89/XII/2013. On the other hand, in the Medan Religious Court Decision, the customer's restructuring request was not used as a basis for consideration, and the panel of judges based their decision more on the Mortgage Law without referring to the DSN-MUI fatwa. This study concludes that there are differences in the judges' paradigms in interpreting sharia financing restructuring, which has implications for the non-uniform application of sharia principles in resolving sharia economic disputes within the Religious Court environment.